Spatially fractionated radiotherapy combined with CapeOX and bevacizumab for postoperative pulmonary metastasis from urachal carcinoma: a case report - Fang, Jian; Wang, Aixin; Yao, Quan; Liu, Xinyi; Zhou, Weiyi; Lang, Jinyi (Frontiers in Oncology, 2025)
Urachal carcinoma is a rare and aggressive malignancy with limited treatment options, particularly in the metastatic setting. Standardized therapeutic protocols are lacking. This case report describes a 62-year-old female patient who developed pulmonary and mediastinal lymph node metastases more than four years after surgical resection of urachal carcinoma. For this case, a combined regimen of Spatially Fractionated Radiotherapy (SFRT), CapeOX (capecitabine plus oxaliplatin) chemotherapy, and bevacizumab targeted therapy was developed. The treatment course was complicated by grade 4 hematologic toxicity and radiation-induced esophagitis, both of which were successfully managed. To our knowledge, this represents the first documented application of SFRT in urachal carcinoma. Although significant tumor shrinkage was not observed, the patient achieved symptomatic relief, metabolic remission, and stable disease during follow-up.